Net Product Lifecycle: Should we reopen the debate before the shortening of life products on the market? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The Product Life Cycle (PLC) is one of the most widely-used marketing conceptsand one of the most strongly-criticized. The lack of conclusive results reduced theinterest in discussing its usefulness in business in the 90’s. Today, the issue has cometo the fore again as a consequence of shorter product life cycles and advances ininformation systems.This article reviews those aspects that led many authors to rely on the PLC when taking business decisions while many others rejected it as an effective predictive tool. The aim of this paper is to determine whether the new business context favours the use of the PLC as a valid tool for defining marketing strategies or whether the limitations identified during the past few decades continue to persist today.
Keywords: Product Life Cycle (PLC); Marketing Strategy; predictive tool